Hypocholesterolaemic and anti-atherogenic effects of palm-based oils (NoveLin I and NoveLin II) in cholesterol-fed rabbits - Che Idris, Che Anishas; Siew, Wai Lin; Abdull Razis, Ahmad Faizal (MDPI, 2020)
NoveLin I and NoveLin II are palm-based oils. NoveLin I has an equal distribution of saturated, monounsaturated and polyunsaturated fatty acids, whereas NoveLin II has a moderate level of monounsaturated fatty acids, and a lower content of saturated and polyunsaturated fatty acids. However, their hypocholesterolaemic and anti-atherogenic effects have not been studied. Therefore, this study aimed to assess the hypocholesterolaemic and anti-atherogenic effects of these oils. Forty male New Zealand White rabbits were divided into four groups and fed with diets containing 35% energy fat with added 0.15% (w/w) dietary cholesterol. Group 1, as the control group (CNO) was fed with a diet containing coconut oil, group 2 and 3 were fed with diets containing either NoveLin I or NoveLin II, and group 4, was fed with diet containing olive oil (OLV) for 100 days. Our results demonstrated that both NoveLin groups have significantly lower total cholesterol and low-density lipoprotein–cholesterol (LDL–C) compared to CNO group and are comparable to the OLV group. Low density lipoprotein–cholesterol/high density lipoprotein-cholesterol (LDL/HDL–C) ratio was significantly lower after the NoveLin II diet but attained significance only in comparison to NoveLin I and CNO groups. Aortic fibrous plaque score was significantly lower in both NoveLin groups compared to CNO group. Our findings suggest that despite the high-fat cholesterol diet, NoveLin II oil resulted in atherogenic effects comparable to olive oil.